2017
DOI: 10.1021/acsbiomaterials.7b00512
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Plug-and-Play Polyurethane Urea Elastomers as Biodegradable Matrixes for Tissue Engineering Applications

Abstract: The highly tunable mechanical properties and resilience of polyurethanes make them promising candidates for tissue engineering applications. Biodegradability is conferred by incorporation of hydrolytically or enzymatically cleavable moieties into the polyurethane structure. A common choice for the biodegradable soft segment is a poly­(ether ester) triblock copolymer synthesized by ring opening polymerization of the polyester from a polyether macroinitiator. Herein, we describe a new “plug-and-play” approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…BPUR was synthesized and electrospun into a thin membrane as previously described. [41] Briefly, a 10 wt% solution of BPUR in 1,1,1,3,3,3hexafluoro-2-propanol (Sigma, St. Louis, MO) was used to electrospin fibrous meshes (flow rate of 0.3 mL min −1 , +7.5 kV at the needle tip, −5 kV at the charged copper plate) under at ambient conditions (25 °C, 45-55% relative humidity). These meshes were evaluated with Fourier transform infrared spectroscopy (FTIR) and characterized with scanning electron microscopy and tensile testing in previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPUR was synthesized and electrospun into a thin membrane as previously described. [41] Briefly, a 10 wt% solution of BPUR in 1,1,1,3,3,3hexafluoro-2-propanol (Sigma, St. Louis, MO) was used to electrospin fibrous meshes (flow rate of 0.3 mL min −1 , +7.5 kV at the needle tip, −5 kV at the charged copper plate) under at ambient conditions (25 °C, 45-55% relative humidity). These meshes were evaluated with Fourier transform infrared spectroscopy (FTIR) and characterized with scanning electron microscopy and tensile testing in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…These meshes were evaluated with Fourier transform infrared spectroscopy (FTIR) and characterized with scanning electron microscopy and tensile testing in previous studies. [11,41] BPUR meshes were sterilized by UV in a culture hood for 1 h before use.…”
Section: Methodsmentioning
confidence: 99%
“…For this instance, many works have been carried out to design a PUs scaffolds for tissue engineering applications. Kishan et al [14] have designed a tri block poly (ether ester) urethane using "plug and play" approach and studied their cycto compatibility and hydrolytic degradation to establish their application in tissue engineering. It was observed that the "plug and play" approach, used for the synthesis of biodegradable PU, gives a platform for highly tunable material aimed at tissue engineering application.…”
Section: Mini Review Tissue Engineeringmentioning
confidence: 99%
“…In the reconstruction of bone tissue, the proper selection of bio-material is an important step in designing and manufacturing biocompatible materials with desirable properties such as bioactivity and biodegradability (Dvir et al, 2011; Salgado et al, 2004). Among various polymers, shape memory polyurethane (SMPU) has attracted considerable attention in tissue engineering regarding its biocompatibility, biodegradability, and antimicrobial properties (Armentano et al, 2010; Kishan et al, 2017; Pandini et al, 2016; Wang et al, 2018; Zhang et al, 2019). Over the course of the last years, several researches have been conducted on the development of SMPU nanocomposites and different nanofillers for various applications and improvement of mechanical, thermal, and chemical properties of SMPU (Babaie et al, 2019; Sultan, 2018).…”
Section: Introductionmentioning
confidence: 99%